Client engagement and building design: the view from actor–network theory. Issue 8 (17th November 2017) - Kurokawa, Megumi; Schweber, Libby; Hughes, Will
ABSTRACT: The accommodation of client expectations in a construction project is challenging. This is, in part, because a client is rarely a single individual and their expectations are rarely static. This paper uses the actor–network theory (ANT) concepts of problematization, enrolment and durability to explore client engagement. The contribution of ANT lies in its (ontological) model of distributed agency, fluid heterogeneous networks and associated effects. A pilot study of a single building project provides an opportunity to theorize the different ways that clients engage in the development of a building. Client engagement differs with the direct versus mediated presence of different client actors, with the devices used to mediate negotiations and with the relative materiality of the network. The findings move the discussion of client engagement beyond the usual calls for better integration to an awareness of the mechanisms by which clients engage. Some decisions are fixed in material objects, while others remain open to ongoing negotiation. There is a need for explicit and continuous interaction and better awareness of when and how decisions are fixed. This would help all participants to deal with the complex and dynamic landscape of people, organizations and interests usually labelled as 'client'.